LC-MS-based lipidomics to examine acute rat pulmonary responses after nano- and fine-sized ZnO particle inhalation exposure. Issue 5 (28th May 2018) - Lee, Sheng-Han; Tang, Chuan-Ho; Lin, Wan-Yu; Chen, Ke-Han; Liang, Hao-Jan; Cheng, Tsun-Jen; Lin, Ching-Yu
Abstract: Zinc oxide (ZnO) nano- and fine-sized particles are associated with respiratory toxicity in humans, but the underlying molecular mechanisms remain unclear. Our previous nuclear magnetic resonance-based metabolomic study demonstrated that changes in phosphorylcholine-containing lipids (PC-CLs) in the respiratory system were associated with ZnO particle-induced respiratory toxicity. However, the details of the lipid species associated with adverse effects and possible biomarker signatures have not been identified. Thus, a liquid chromatography-mass spectrometry (LC-MS)-based lipidomics platform was applied to examine the alterations of PC-CL species in the lungs of rats treated with a series of concentrations of nano-sized (35 nm) or fine-sized (250 nm) ZnO particles via inhalation. Principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), and the Mann–Whitney U (MWU) test with false discovery rate (FDR) control were conducted to explore the perturbed lipid species and to discriminate a potential pulmonary biomarker signature after ZnO particle exposure. The PCA and PLS-DA models revealed that the fine-sized ZnO particle-treated groups and the high-concentration nano-sized group were separated from the control groups as well as from the low and moderate nano-sized groups. The results from the MWU test further suggested that after FDR adjustment, numerous PC-CL species were altered in the high-concentration and moderate-concentration fine-sized groups. Furthermore, our results suggested that lipids involved in anti-oxidation, membrane conformation, and cellular signal transduction were altered in response to ZnO-induced oxidative stress and inflammation. One lipid, PC(18:0/18:1), exhibited good performance (AUC > 0.8) of discriminative ability in distinguishing ZnO particle exposure from the control. These findings not only provide a foundation for the exploration of possible ZnO particle-mediated mechanisms but also suggest a lipid biomarker for ZnO particle exposure.